Effect of expiratory muscle training on peak cough flow in children and adolescents with cystic fibrosis - Emirza, Cigdem; Aslan, Goksen Kuran; Kilinc, Ayse Ayzit; Cokugras, Haluk Cezmi (European Respiratory Soc Journals Ltd, 2020)
[Abstract Not Available]
Keywords: Cystic Fibrosis; Cough; Rct (Randomized Controlled Trial)